Two Magical Spaces? – Aflitos Stadium and Arena Pernambuco under Marc Augé’s Anthropology of Supermodernity view - Ferreira, Bruno Rafael Torres; Leão, André Luiz Maranhão de Souza (Revista de Administração da UFSM, 2019)
Having the arenas construction for the FIFA World Cup Brazil, Clube Náutico Capibaribe’s fans meets in the middle of a major change scenario: on one hand, the old stadium, laden with affective meanings; on the other, Arena Pernambuco, product and stage of new consumption patterns linked to football in contemporary society. Following Marc Augé’s Anthropology of Supermodernity as theorethical lens, from an approach aligned to the Consumer Culture Theory (CCT), we undergone present ethnographic study, in the period of game exchange mands from one stadium to other, in order to understand such stadium symbolic constructions as identity spaces for the blank-red supporters. We observed that Aflitos is a space with strong identity ties with the fans. Arena Pernambuco, however, began only seen as a modern space, but became to have its characteristics and new habits gradually assimilated.